Effects of cysteine, asparagine, or glutamine limitations in Chinese hamster ovary cell batch and fed‐batch cultures. (19th December 2019) - Ghaffari, Navid; Jardon, Mario A.; Krahn, Natalie; Butler, Michael; Kennard, Malcolm; Turner, Robin F. B.; Gopaluni, Bhushan; Piret, James M.
Abstract: Amino acid availability is a key factor that can be controlled to optimize the productivity of fed‐batch cultures. To study amino acid limitation effects, a serum‐free chemically defined basal medium was formulated to exclude the amino acids that became depleted in batch culture. The effect of limiting glutamine, asparagine, and cysteine on the cell growth, metabolism, antibody productivity, and product glycosylation was investigated in three Chinese hamster ovary (CHO) cell lines (CHO‐DXB11, CHO‐K1SV, and CHO‐S). Cysteine limitation was detrimental to both cell proliferation and productivity for all three CHO cell lines. Glutamine limitation reduced growth but not cell specific productivity, whereas asparagine limitation had no significant effect on either growth or cell specific productivity. Neither glutamine nor asparagine limitation significantly affected antibody glycosylation. Replenishing the CHO‐DXB11 culture with cysteine after 1 day of cysteine limitation allowed the cells to partially recover their growth and productivity. This recovery was not observed after 2 days of cysteine limitation. Based on these findings, a fed‐batch protocol was developed using single or mixed amino acid supplementation. Although cell density and antibody concentration were lower compared to a commercial feed, the feeds based on cysteine supplementation yielded comparable cell specific productivity. Overall, this study showed that different amino acid limitations have varied effects on the performance of CHO cell cultures and that maintaining cysteine availability is a critical process parameter for the three cell lines investigated.